Ascidians collected during the Madibenthos expedition in Martinique: 2. Stolidobranchia, Styelidae - Monniot, Françoise (Zootaxa, 2018)
An inventory of the marine benthic fauna around Martinique was the aim of the European Madibenthos expedition 2016. Among a large number of invertebrates abundant ascidians were collected: the phlebobranchs were already studied and the results published (Monniot 2018). A second group, belonging to the Styelidae (Stolidobranchia), includes 17 species of which one is new and new records for two other species. Each of them is described and the geographic distribution given.